A Comparative Study of Quantity and Scheduling Using 4D BIM and Conventional Methods in Column, Beam, and Slab Construction - Muzaffar, Risal; Putra, I Nyoman Dita Pahang; Junianda Velantika, Griselda (Departement of Civil Engineering, Universitas Winaya Mukti, 2025)
Inadequacies in the conceptualization and assessment of construction scheduling frameworks can disrupt the epistemic continuity of project execution, thereby undermining procedural coherence and operational efficiency. Accurate and detailed material quantity planning is essential to ensure precise resource forecasting and the development of efficient and reliable construction schedules. This research investigates the role of methodological selection in the accuracy and efficiency of construction planning, with a particular emphasis on material quantification and scheduling outcomes through this comparative framework. The methodological approach undertaken in this study involves quantity surveying practices through the application of two modelling-based techniques, namely CAD-Revit and CAD-Conventional. For construction-shop drawing documentation as the primary data source, material quantities derived from each method serve as the basis for schedule development. This process culminates in the integration of 4D Building Information Modelling to facilitate the temporal visualisation of construction sequences, which supports a more comprehensive evaluation of the implications associated with each quantity derivation method on the accuracy of project planning. The comparative analysis of material quantities derived from the two methods revealed significant fluctuations, with the CAD-Revit approach demonstrating greater efficiency in material usage. This variation was further reflected in the scheduling outcomes, where the 4D BIM methodology indicated divergent timelines for the completion of structural component progress across different floors.